Interface pressure in transtibial socket during ascent and descent on stairs and its effect on patient satisfaction - Ali, S.; Abu Osman, Noor Azuan; Eshraghi, A.; Gholizadeh, H.; Abd Razak, N.A.B.; Wan Abas, Wan Abu Bakar (2013)
Background Transtibial amputees encounter stairs and steps during their daily activities. The excessive pressure between residual limb/socket may reduce the walking capability of transtibial prosthetic users during ascent and descent on stairs. The purposes of the research were to evaluate the interface pressure between Dermo (shuttle lock) and Seal-In X5 (prosthetic valve) interface systems during stair ascent and descent, and to determine their satisfaction effects on users. Methods Ten amputees with unilateral transtibial amputation participated in the study. Interface pressure was recorded with F-socket transducer (9811E) during stair ascent and descent at self-selected speed. Each participant filled in a questionnaire about satisfaction and problems encountered with the use of the two interface systems. Findings The resultant mean peak pressure (kPa) was significantly lower for the Dermo interface system compared to that of the Seal-In X5 interface system at the anterior, posterior and medial regions during stair ascent (63.14 vs. 80.14, 63.14 vs. 90.44, 49.21 vs. 66.04, respectively) and descent (67.11 vs. 80.41, 64.12 vs. 88.24, 47.33 vs. 65.11, respectively). Significant statistical difference existed between the two interface systems in terms of satisfaction and problems encountered (P < 0.05). Interpretation The Dermo interface system caused less pressure within the prosthetic socket compared to the Seal-In X5 interface system during stair negotiation. The qualitative survey also showed that the prosthesis users experienced fewer problems and increased satisfaction with the Dermo interface system.